Material Characterization of Luminescent Down-Shifting Layers for Solar Cells Application - GILLIGAN, SARAH (Trinity College Dublin. School of Engineering. Disc of Civil Structural & Environmental Eng, 2019)
High energy photons in the UV region are not efficiently used in solar cells and limit the overall efficiency of the cell. Luminescent Down-Shifting (LDS) layers can be used to convert the high energy photons to a lower energy before it reaches the cell, which is more efficiently absorbed. In this study, an investigation of the optics of polymer thin-films LDS layer when comprising of mixed organic dyes, against single dye thin-films was investigated. The effect of creating a layer comprising of an equal ratio of BASF Lumogen Yellow 083, Lumogen Orange 240, and Lumogen Violet 570 in a polymethyl methacrylate (PMMA) polymer was investigated and compared to the experimental results from each single dye. This aided in determining whether using multiple organic dyes in a single film was beneficial for use as an LDS material. The concentration of each individual dye was then optimised with the EQE determined and then tested outdoors over three months. There was a large degradation of the thin films in the short range of time, so due to the limitations of Lumogen dyes, focus moved to quantum dots (QDs). The absorption, emission, and quantum yield of a range of QDs was determined for introduction into the Lumogen layers.
APPROVED
Keywords: Solar; Luminescent Down-Shifting; Lumogen